The dogs - Stratton, Allan 1951- (Penguin Books Australia, 2015)
Set in a remote part of the Canadian countryside, THE DOGS is a first person narration by 15 year old Cameron. He and his mother have just moved yet again to keep out of the way of Cameron's violent father. This time their new 'home' is a deserted old farmhouse with a disturbing history